Formação em tomada de decisão compartilhada de estudantes de medicina na graduação: uma análise na Universidade Federal do Tocantins - Pedreira, Paulo Geovanny (Universidade Federal de São Paulo, 2023)
Introduction: Shared decision making (SDM) is an approach in which physicians and patients share the best available evidence when faced with the task of making decisions, in wich patients are supported to consider options in order to obtain preferences. Despite being increasingly incorporated into the medical education curriculum, there is not much evidence of which strategies are most effective for instructing medical students on Patient Centered Care (PCC) and SDM during their undergraduate course, especially in internship. Objectives: To analyze the training in shared decision making in the undergraduate medical course at the Tocantins Federal University (UFT). Methods: Documental analysis of the pedagogical project of the UFT medical course and 118 documents of a collegiate meeting to investigate a training proposal regarding the development of competences related to PCC and SDM. To analyze the learning in SDM, two stages of data collection were carried out: application of a Likert type attitudinal scale with 116 interns of the medical clinic internship; and in depth interview conducted with 7 interns and 7 professors of the Medicine course at UFT. Results: Documentary analysis of the pedagogical project of the UFT medical course and 2 documents of the collegiate meeting showed that training based on pedagogical course project is still incipient, especially if we take into account the teaching of SDM. However, indirect indications of preparation for the perspective of care based on the integrality of the subject were found. The combined results of the attitudinal scale and in depth interviews showed the participants' perceptions: impairment in the teaching of SDM before and during the medical clinic internship; loss of teaching communication skills and considerations of emotional aspects and preferences of patients, however, they already say that it stimulates the formation of the student in communication skills and patient preferences. Respondents recognize that medical students, especially interns, are harmed in terms of granting autonomy to approach the patient for SDM. About the teaching of SDM in the pre boarding stage, the interviewees recognize the formal teaching of SDM in the pre boarding stage, but in a deficient way, and the approach to teaching in the form of a hidden curriculum is very present. During the medical internship, the interviewees recognize that there is planned teaching of SDM during the practices in the form of case discussion, welcoming practices and consideration of the patient's preferences based on evidence, however the presence of teaching in the form of a hidden curriculum is also very evident. Respondents recognize that the lack of approach to SDM teaching is due to the lack of time caused by the high demand of patients and the deficiency in the qualification of preceptors in patient centered methodologies; recognize that in the medical clinic internship there is little role for the medical intern to perform SDM, often accentuated by the hierarchy of teaching scenarios, where the resident has the preference in patient management. Conclusions: Even with the emergence of curricular matrices theoretically focused on PCC, its implementation and development in medical schools has been a major challenge for educational institutions. Although the UFT Medicine curriculum points to patient centered actions, both theoretical and mainly practical training as in internship, reveals weaknesses and challenges to be overcome. In internship practices, the student's relationship with the patient tends to be closer, with important recognition of their values, whether emotional, cultural and affective, which can mark their future praxis in the therapeutic relationships that they will develop throughout their career.